2012
DOI: 10.33549/physiolres.932224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Ketamine-Dexmedetomidine and Sevoflurane-Sufentanil Anesthesia on Cardiac Biomarkers After Cardiac Surgery: An Observational Study

Abstract: Inhalational anesthetics have demonstrated cardioprotective effects against myocardial ischemia-reperfusion injury. Clinical studies in cardiac surgery have supported these findings, although not with the consistency demonstrated in experimental studies. Recent investigations have questioned the advantages of inhalational over intravenous anesthetics with respect to cardiac protection. Ketamine has been shown to be comparable with sufentanil, and has even demonstrated anti-inflammatory properties. Dexmedetomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Ji et al showed an improvement in mortality rate with iv dexmedetomidine infusion in patients undergoing CABG surgery (9). Riha et al found that the coadministration of dexmedetomidine-ketamine was associated with lower blood levels of cTnI and CKMB than sevofluranesufentanil anesthesia in patients undergoing elective CABG surgery (16).…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al showed an improvement in mortality rate with iv dexmedetomidine infusion in patients undergoing CABG surgery (9). Riha et al found that the coadministration of dexmedetomidine-ketamine was associated with lower blood levels of cTnI and CKMB than sevofluranesufentanil anesthesia in patients undergoing elective CABG surgery (16).…”
Section: Discussionmentioning
confidence: 99%
“…Four trials evaluated ketamine's effects on postoperative myocardial injury through either troponin levels or electrocardiogram criteria. [ 28 33 34 35 ] Two of these trials suggested that ketamine decreases myocardial injury after surgery.…”
Section: Brief Historymentioning
confidence: 99%
“…8 Our study showed decreased levels of CKMB in DP group than the P group, albeit,not statistically significant, but it does indicate that the combination therapy is at least not harmful for the ischemic hearts. Riha et al 23 also reported decreased CKMB levels in cardiac surgery patients when they used DEX.…”
Section: Discussionmentioning
confidence: 95%